2006
DOI: 10.1002/chin.200627229
|View full text |Cite
|
Sign up to set email alerts
|

Perturbational Statistical Theories of Magnetic Fluids

Abstract: The theories that account for the colloidal structure of a magnetic fluid give far better results than the gas-type or mean-field models. We show this by using standard perturbative approaches of colloidal science and expressing the magnetization M(H) and the initial magnetic susceptibility χ as Taylor series about the Langevin values M L (H) and L χ . One of the methods surveyed enables the structural study of the ferrocolloid through the analysis of the pair distribution function. We give a polar plot of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…For zero field (α = 0), substituting L 3 (0) = 0 in to Eq. (18) confirms that β 02 (x) = γ 02 (x)/3 coincides with the isotropic function derived in Ref. 35 and listed in Table I.…”
Section: Field-dependent Pdf Expansion Coefficientssupporting
confidence: 90%
See 1 more Smart Citation
“…For zero field (α = 0), substituting L 3 (0) = 0 in to Eq. (18) confirms that β 02 (x) = γ 02 (x)/3 coincides with the isotropic function derived in Ref. 35 and listed in Table I.…”
Section: Field-dependent Pdf Expansion Coefficientssupporting
confidence: 90%
“…10 Field-induced anisotropies in particle correlations have been examined previously by scattering experiments, [11][12][13][14][15] theory, 14,[16][17][18][19][20] and computer simulation. [20][21][22][23] There are, of course, existing theories for the structures of ferrofluids.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the long range interparticle correlation on the magnetically induced dichroism and birefringence in magnetic colloids was theoretically described in Refs. [9,10] respectively. These two classes of models, based on particle agglomeration and long range interparticle correlation, predict the possibility of magnetically induced optical anisotropy in magnetic colloids made of spherical particles as well as a nonlinear dependence of dichroism and birefringence on the particle concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Using the pair correlation function in a colloidal suspension of magnetic nanoparticles developed by Ivanov and Kuznetsova [11], Popescu and Socoliuc [9] derived the magnetic colloid absorption coefficient for light polarized parallel and perpendicular to the magnetic field, which allowed for the description of the magnetically induced linear dichroism dependence on magnetic particle size and concentration. It was found that the dichroism has a nonlinear dependence on the magnetic particle concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation